The impact of social comparisons on reciprocity - Simon Gächter; Daniele Nosenzo; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
This paper investigates how social comparison information about referent others (i.e. learning what similar others do and how they are treated) affects reciprocal relationships. Using a three-person gift-exchange game we study how employees' reciprocity towards an employer is affected by exposure to pay comparison information (what co-workers earn) and effort comparison information (how co-workers perform). We find that pay comparison information comparison information (how co-workers perform). We find that pay comparison information does not affect reciprocity. Effort comparison information, however, influences reciprocal relationships in important ways: the ability to observe reciprocal behavior on the part of others strongly affects employees' reciprocity towards the employer. While our data show that social information in principle may either erode or amplify reciprocal relationships, we find that, on average, social comparisons have a detrimental impact on reciprocity.
Keywords: A13; C92; J31; 330; reciprocity; gift-exchange; social information; social comparisons; pay comparisons; Soziale Beziehungen; Austauschtheorie (Soziologie); Arbeitsplatz; Arbeitskräfte; Lohn; Information; Vergleich; Spieltheorie